2021
DOI: 10.3390/foods11010064
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Customer Decisions to Use Online Food Delivery Service during the COVID-19 Pandemic

Abstract: Despite the popularity of online food delivery systems in the foodservice industry, there have been few studies into customers’ decision-making process to use online food delivery services during the Coronavirus disease (COVID-19) pandemic. This study applied the technology acceptance model (TAM) to examine the factors affecting customers’ intention to use online food delivery services. Results showed (a) the perceived usefulness affects customer’s online food delivery usage directly and indirectly through cus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 56 publications
(125 reference statements)
4
42
0
1
Order By: Relevance
“…Jun et al [30] reported that consumers in the US were more likely to use OFDSs since the Pandemic and indicated that further research was warranted both in other cultural settings and in a larger geographical setting. The same study was focused on consumer acceptance of technology leaving a gap regarding the intention to use OFDSs, and recommended further exploration in that area.…”
Section: Research Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Jun et al [30] reported that consumers in the US were more likely to use OFDSs since the Pandemic and indicated that further research was warranted both in other cultural settings and in a larger geographical setting. The same study was focused on consumer acceptance of technology leaving a gap regarding the intention to use OFDSs, and recommended further exploration in that area.…”
Section: Research Gapmentioning
confidence: 99%
“…The flexibility to use OFDSs provides opportunities for people to conduct transactions whenever and wherever possible, and previous research has identified perceived ease of use as an important factor in consumer use of ODFSs; this is reported as a gap in the existing literature and is a suggested area for further research [30]. Consumers are often motivated by time constraints when making purchase decisions and are more likely to engage in OFDSs if they perceive the process as easy [57,58].…”
Section: Hypothesis 2 (H2) Convenience Motivation Positively Impacts Consumers' Intention To Use MDmentioning
confidence: 99%
“…Studies of HMRs from a nutritional perspective have mostly focused on the nutritional balance and quality of HMRs, e.g., [ 3 , 22 , 23 ]. Despite HMR-related research achievements in various academic fields, research to understand the characteristics of products is essential in seeking a sustainable service strategy of COVID-19 [ 24 , 25 ]. The IPA model is used as a significant model for evaluating service quality performance and predicting consumer behavior [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this Special Issue was, for the first time, to bring together researchers with key insights on how COVID-19 has impacted appetite and eating behaviours, from the fundamental to the applicable, as assessed by human sensory perception and behaviour [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we requested the inclusion of a range of research from fundamental effects on the senses, to changes in consumer preferences all the way to how and why COVID-19 has changed consumer behaviours in relation to food and eating in the longer term [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%